2016
DOI: 10.1186/s12983-016-0148-y
|View full text |Cite
|
Sign up to set email alerts
|

Egg rejection in blackbirds Turdus merula: a by-product of conspecific parasitism or successful resistance against interspecific brood parasites?

Abstract: BackgroundTraditional theory assumes that egg recognition and rejection abilities arise as a response against interspecific brood parasitism (IBP). However, rejection also appears in some species that are currently not exploited by interspecific parasites, such as Turdus thrushes. Recent evidences suggest that rejection abilities evolved in these species as a response to conspecific brood parasitism (CBP). To test these two alternative hypotheses, we performed an experimental study by parasitizing nests of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 98 publications
(164 reference statements)
2
26
0
Order By: Relevance
“…Our results show that the Chestnut Thrush has a moderate egg rejection ability, which is similar to results from European studies of the Song Thrush and the Blackbird (Grim and Honza 2001). Conversely, we show that the Chinese Thrush has a strong egg recognition ability, which is similar to that of the Spanish Blackbird (Soler et al 2015;Ruiz-Raya et al 2016) and the Grey-backed Thrush in eastern China (Yang et al 2019b;Zhang et al 2019). Many potential hosts, even if not parasitized currently, may have retained an ability to reject eggs from a history with the parasite (Peer and Sealy 2004).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Our results show that the Chestnut Thrush has a moderate egg rejection ability, which is similar to results from European studies of the Song Thrush and the Blackbird (Grim and Honza 2001). Conversely, we show that the Chinese Thrush has a strong egg recognition ability, which is similar to that of the Spanish Blackbird (Soler et al 2015;Ruiz-Raya et al 2016) and the Grey-backed Thrush in eastern China (Yang et al 2019b;Zhang et al 2019). Many potential hosts, even if not parasitized currently, may have retained an ability to reject eggs from a history with the parasite (Peer and Sealy 2004).…”
Section: Discussionmentioning
confidence: 62%
“…Scholars have recently examined whether thrushes are suitable hosts for cuckoos and the evolution of their egg recognition ability (Grim et al 2011;Samǎs et al 2014;Soler 2014b;Ruiz-Raya et al 2016). Insectivorous birds that have large populations and build open nests are generally considered suitable hosts for cuckoos (Soler et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Also, another blackbird study found that the number of touches in a nest did not vary after the introduction of a conspecific (i.e. highly mimetic) egg, whereas they increased significantly following the introduction of a non-mimetic egg [ 46 ]. Thus, to study the relationships between recognition and ejection we have assumed that egg-touching indicates recognition and, to be conservative, we considered an experimental egg to have been recognized (even if it was not ejected) when it was touched more frequently than in 95% of control nests (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…However, Soler (2014a) stated that, to date, there is no evidence of CBP causing egg rejection in thrushes per se , though Samas et al (2014b) subsequently supported their conclusion with empirical evidence. Similarly, Ruiz-Raya et al (2016) investigated recognition of conspecific or heterospecific eggs in European blackbirds by manipulating the risk of CBP and IBP, respectively. They found that blackbirds presented low recognition of conspecific eggs even under high risk of CBP, and thus their results supported the IBP hypothesis that egg recognition has evolved and is maintained in blackbirds as a response to previous cuckoo parasitism.…”
Section: Dear Editormentioning
confidence: 99%
“…However, Samas et al (2014b) argued that a theory is never out of date and addressed the theoretical objections by empirical evidence. Recently, Ruiz-Raya et al (2016) further tested egg recognition in blackbirds by manipulating the risk of CBP and IBP and concluded that selection from IBP likely accounts for egg recognition in blackbirds.…”
Section: Dear Editormentioning
confidence: 99%